Implications on the introduction of transgenics in Brazilian maize breeding programs - Parentoni,Sidney Netto (2013)
Transgenic maize was approved in Brazil in 2008/2009. In 2012, it occupied 73% of the country maize growing area. This high adoption rate confirms studies indicating that technology use has been the major driving force in Brazilian agriculture. Maize seed market in the world has been a concentrated sector. Although, when this sector is associated with transgenesis, this concentration increases sharply. In one side, there is the idea that companies can benefit from gains of scale and complementarities to maximize their efficiency in research and development (R&D). On the other side, this concentration may allow the exercise of "market power" by dominant companies. The objective of this study is to analyze the impacts of the adoption of transgenic technology in the arrangements of maize breeding programs and seed production sector in Brazil. A critical analysis of the situation of the breeding programs that do not have this technology is made.